Produktivitas dan Faktor-Faktor yang Berpengaruh Terhadap Produksi Usahatani Tomat (Solanum lycopersicum Mill) di Kabupaten Jember - Bagus Rangga Sita; Syamsul Hadi; Edy Sutiarso (STIE Mandala Jember, 2018)
The purpose of this study include: 1)measuring the level of farm productivity and comparing among the tomato business scale, and 2) to identify factors that influence the tomato farm production in Jember. This research has been conducted in Jember, covering five District of samples, namely: Ledokombo, Sumberjambe, Ajung, Panti and Umbulsari. The data used are primary data and secondary data. Primary data were obtained from interviews with tomato farmers are guided by a list of questions that had been developed previously. While the secondary data obtained from the literature and agencies associated with this research. Analysis of the data used include quantitative descriptive analysis and regression naturally assuming that the relationship between the independent variables (Xi) and dependent variable (Y) is a Cobb-Douglas production function. The final conclusion is that: 1) The average productivity of farming tomatoes in Jember district, which consists of land productivity amounted to 153.662 ku / ha, labor productivity of 4.906 Kg / JKP, and productivity costs by 0.00047 Kg/USD. Based strata land area, did not show any differences in labor productivity and costs and but on land productivity among business scale narrow and wide, showed a highly significant difference in the confidence level of 99%, and 2) the factors that affect significantly to namely the production of land, labor and seed, while the fertilizers, pesticides and pesticide effect no significant effect on farm production of tomatoes in Jember. Keywords: Productivity, Production, and comparisons between the scale of farming